Profile of Higher Order Thinking Skills (HOTS) of Class IV Students on Energy Resources at Ma'arif Sentul: Profil Higher Order Thinking Skills (HOTS) Siswa Kelas IV Pada Materi Sumber Energi Di Ma’arif Sentul - Ayu Ashmatur Rohmah; Fitria Eka Wulandari (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study is to describe the profile of Higher Order Thinking Skills (HOTS) in grade IV students on Energy Sources at MI Ma'arif Sentul. The research method used in this study is a survey type research method, the population used is all students of MI Ma'arif Sentul, with a sample of 23 students taken randomly which can be obtained from calculations using the slovin formula. The data collection technique used is a test. The research instrument used is a matter of higher order thinking skills. The test results were then analyzed using the formula for higher order thinking skills (HOTS) and described into 3 criteria, namely analyzing, evaluating, and creating. Based on the results of the analysis, it can be concluded that students at MI Ma'arif Sentul have high order thinking skills (HOTS) at a good level in energy source material.